1984
DOI: 10.1073/pnas.81.15.4856
|View full text |Cite
|
Sign up to set email alerts
|

Guatemalan forest synthesis after Pleistocene aridity

Abstract: Sediments from two lakes in the Peten Department, Guatemala, provide palynological evidence from Central America of late Pleistocene aridity and subsequent synthesis of mesic forests. Late Glacial vegetation consisted of marsh, savanna, and juniper scrub. An early Holocene temperate forest preceded a mesic tropical forest with Brosimum (ramon). Thus "primeval" rain forests of Guatemala are no older than 10,000 to 11,000 years and are considerably younger Holocene (10,[0][1][2][3][4][5][6][7][8]500 B.P.) (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
2
5

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 22 publications
4
105
2
5
Order By: Relevance
“…Similarly, a strong aridity signal is directly recorded by low lake levels in central México due to reduced northern excursion of the ITCZ, trade wind circulation, and ensuing reduced oceanic-land moisture transfer (Markgraf et al, 2000) that would have been reflected in ecosystem response. For example, forest on the Pacific side of the Central America contained a mosaic of high and low altitude forest species; a similarly novel type of forest has also been shown for Mera, Ecuador (Liu and Colinvaux, 1985) and Peten, Guatemala (Leyden, 1984). Of the two sites that record the warm evergreen forest biome at this period a site in Guatemala was dominated by Chenopodiaceae, Juniperus, Pinus and Quercus.…”
Section: 000±1000 14 C Yr Bpmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, a strong aridity signal is directly recorded by low lake levels in central México due to reduced northern excursion of the ITCZ, trade wind circulation, and ensuing reduced oceanic-land moisture transfer (Markgraf et al, 2000) that would have been reflected in ecosystem response. For example, forest on the Pacific side of the Central America contained a mosaic of high and low altitude forest species; a similarly novel type of forest has also been shown for Mera, Ecuador (Liu and Colinvaux, 1985) and Peten, Guatemala (Leyden, 1984). Of the two sites that record the warm evergreen forest biome at this period a site in Guatemala was dominated by Chenopodiaceae, Juniperus, Pinus and Quercus.…”
Section: 000±1000 14 C Yr Bpmentioning
confidence: 60%
“…This appears to be a regional signal as early Holocene evergreen forests of northern Venezuela were replaced by semi-deciduous elements during the mid-Holocene (Leyden, 1984). Enhanced precipitation 756 R. Marchant et al: Pollen-based biome reconstructions for Latin America over Central America would have been accompanied by a northward shift of the ITCZ, enhanced southerlies and cooler equatorial sea surface temperatures .…”
Section: ±500 14 C Yr Bpmentioning
confidence: 99%
“…Seasonal southward displacement during cooling events of the ITCZ results in reduced precipitation in the area. The regional trend of drier Pleistocene climates is further supported by evidence from Guatemala (Leyden, 1984) and Panama (Markgraf, 1989;Bush et al, 1992).…”
Section: Palaeoenvironmental Reconstructionmentioning
confidence: 72%
“…Pollen analysis of Lake Quexil Core 80-1 indicated that glacialage vegetation was dominated by temperate xeric thorn scrub, suggesting that Peté n climate was colder and drier during glacial periods of the late Pleistocene (Leyden, 1984;Leyden et al, 1993Leyden et al, , 1994. The finding had important ecological implications because it indicated that Peté n's seasonal tropical forest is no older than $11 ka (Deevey et al, 1983;Leyden, 1984).…”
Section: Article In Pressmentioning
confidence: 99%